Biogas and Biomass Implementation in Rural Areas - Sandim,Álvaro A. (2019)
Abstract Advances in energy demand in rural areas cannot be dissociated from agricultural modernization, large estates, mechanization of labor and reduced investment in small production. The use of biogas together with biomass are the most cost-effective ways for the small producer, as it has a high calorific value. In the case of biogas the procedure is performed by combining a compressor and a chiller, allowing the gas enter the reactor and burn together with the air stream. The use of these techniques is an auxiliary way to reduce the cost of the producer to produce a certain crop, besides allowing a participation in the final energy supply, so that the utilities have an alternative to distribute the surplus energy to another region, serving thus a wider range in the rural area.